An Organizational Culture, Leadership Style And Innovative Behaviour on Performance of the Organization - Abdul Wahab Samad (Journal of Center for Energy Policy and Human Resources Capacity Development, 2025)
This study intends to explore the impact of organisational culture, leadership style, and innovation practices on employee performance within a public sector organisation. This research employs a qualitative methodology through document analysis to investigate a range of references, publications, and reports. The study aims to elucidate the relationship between adaptive organisational culture, supportive leadership styles, and the innovation practices that emerge among employees. The findings indicate that a robust organisational culture, coupled with an inspirational leadership style, is instrumental in cultivating innovative practices, which subsequently have a beneficial impact on employee performance. This study underscores the significance of cultivating a culture that fosters creativity and innovation, alongside the provision of effective leadership training to enhance organisational performance. The findings of this research suggest that organisations ought to prioritise the establishment of a culture conducive to innovation and to equip their leaders with the requisite skills to inspire and empower employees. This approach is likely to enhance productivity and facilitate the more effective attainment of organisational objectives